Hubungan Antara Asupan Protein, Vitamin C, dan Kebiasaan Minum Teh Dengan Kejadian Anemia pada Remaja Putri di SMA Negeri 1 Mojolaban, Kabupaten Sukoharjo Jawa Tengah - Utomo, Gulit Danan Prasetyo; , Endang Nur Widyaningsih, S.ST.,M.Si,Med; , Mutalazimah, SKM., M.Kes (2013)
Background: Anemia is cused by lack of hemoglobin, which means also lack of oxygen throughout the body. Women are more prone to anemia, especially in adolescence. Prevalence of anemia data was taken from health department of Sukoharjo in 2008 as many as 28%, in 2009 asa many as 33,84%, and in 2010 as many as 48%. Purpose: To know correlation between intake protein, vitamin C, and drinking habits of tea with Hemoglobin Levels in females student at state 1 high school of Mojolaban sukoharjo regency. Method of the Research: The research implemented a survey-observational with cross-sectional approach. Subject of the research is 33 individuals selected by using propotional random sampling. Data of intake protein, vitamin C, and drinking habits of tea was taken by recall procedures with 3x24 hour by random day and data of hemoglobin concentration by hemoque methode. Data is analyzed by using correlation test of Pearson-product moment. Result: Based on univariate analysis, most levels of protein intake are included in the category of research subjects less as many as 81.8%, most of the intake levels of vitamin C research subjects included in the category of less as many as 63.6%, research subjects with daily consumption of tea as much as 60.6%. The results of hemoglobin levels 36.4% of normal subjects, whereas hemoglobin levels are not normally subject to 63.6%. The results of Pearson product moment correlation test p value = 0.870, p=0,198, p=0,455 Conclusion: It can be concluded that there is no correlation between intake protein, vitamin C, and drinking habits of tea with hemoglobin levels in females student at state 1 high school of Mojolaban Sukoharjo regency.